HISTORICAL FACTORS OF INFLUENCE ON POLITICAL CALTURE OF MODERN UKRAINIAN SOCIETY - Топалова, С.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article is devoted to the analysis of the basic ways and means of activization of historical factors which influence the process political culture transformation in Ukrainian society. The specificity of use of historic factors in modern political technologies and campaigns, consequences of their influence on mass and group political culture has been considered.